2008
DOI: 10.1080/15569520802327807
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Ocular, Pulmonary, and Cutaneous Complications of Mustards in Patients in the City of Sardasht, Iran

Abstract: The purpose of our study was to evaluate the late ocular, pulmonary, and cutaneous complications of mustards, 19 years after exposure in 600 patients of the city of Sardasht, Iran. In this case study, we evaluated 600 warfare patients aged 19 to 80 years whose mustard gas injury dated back to 19 years before evaluation in Sardasht. Our results showed that 5.2% of our cases were aged 19-20 years, 18.5% were aged 21-30 years, 31.7% were aged 31-40 years, 23.5% were aged 41-50 years, 12.2% were aged 51-60 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In a large cohort of MG exposure victims in Sardasht, Iran, Ghassemi‐Broumand et al . (2008) showed that late mild pulmonary complications were more frequent than mild ocular and cutaneous complications; however, moderate ocular complications were more frequent than moderate pulmonary and cutaneous complications.…”
Section: Eye Injurymentioning
confidence: 99%
“…In a large cohort of MG exposure victims in Sardasht, Iran, Ghassemi‐Broumand et al . (2008) showed that late mild pulmonary complications were more frequent than mild ocular and cutaneous complications; however, moderate ocular complications were more frequent than moderate pulmonary and cutaneous complications.…”
Section: Eye Injurymentioning
confidence: 99%
“…The exposures were confirmed based on the documented previous military history and medical records of participants. Based on the chart of the Iranian Ophthalmic Foundation of Martyrs and Veterans Affairs [20], those veterans who were categorized as severe SM induced ocular involvement were invited to participate in this study from all provinces of Iran. Common ocular findings in this group include corneal ischemia, vascular abnormalities, neovascularization, melting, thinning, hyaline deposition, or diffuse corneal opacity [21].…”
Section: Methodsmentioning
confidence: 99%
“…Complaints during chronic phase include itching, burning sensation, photophobia, tearing, decreased vision, dry eye, red eye, ophthalmic pain and foreign body sensation. 19,63,65 An important ocular phenomenon known as delayed-type ulcerative keratitis may happen in some cases. It is characterized by corneal thinning, opacification, neovascularization and epithelial deficiency leading to photophobia, lacrimation, failing vision and late-onset blindness.…”
Section: Chronic Eye Injurymentioning
confidence: 99%